Words Are Essential, but Underexamined, Research Tools for Microbes and Microbiomes - Erika Szymanski (American Society for Microbiology, 2021)
Language constitutes an essential set of scientific construction tools, not only for communicating knowledge, but for conceptualizing the world. Metaphors in particular, as conventions that guide and reproduce analogical reasoning, merit attention that they largely do not receive.